1999
DOI: 10.1002/(sici)1096-8652(199903)60:3<185::aid-ajh3>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Serum macrophage colony-stimulating factor (M-CSF) level is elevated in patients with old cerebral infarction related to vascular damage

Abstract: We measured the serum levels of macrophage colony-stimulating factor (M-CSF) in 37 patients with an old cerebral infarction who had been surmised to have a damaged vessel wall and who had been in a stable condition for over three months after stroke onset, and those of 41 healthy control subjects. The M-CSF levels in the patients were significantly higher (P < 0.01) than those of the controls at 1320.4 +/- 410.6 unit/ml and 853.9 +/- 180.3 unit/ml, respectively. The plasma levels of von Willebrand factor (vWF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…CSF-1 plays an important role in atherosclerosis formation, as reviewed by Andrés et al 39 Elevated levels of CSF-1 have previously been reported in patients with an old stroke, 40 but this is the first study describing a link with incident ischemic stroke.…”
Section: Macrophage Colony-stimulating Factormentioning
confidence: 95%
“…CSF-1 plays an important role in atherosclerosis formation, as reviewed by Andrés et al 39 Elevated levels of CSF-1 have previously been reported in patients with an old stroke, 40 but this is the first study describing a link with incident ischemic stroke.…”
Section: Macrophage Colony-stimulating Factormentioning
confidence: 95%